Kathak Dance–Based Cultural Values and Teaching Effectiveness among Secondary School Teachers - Aryan Sharma; Priyanka Kumari; Aditya Singh; Shalini Tyagi (PT. Intelektiva Global Nusantara, 2026)
Cultural values embedded in traditional performing arts have long played an important role in shaping educational practices in India. Among these traditions, Kathak dance represents a classical art form rooted in storytelling, rhythm, discipline, and expressive communication, which are pedagogically relevant to classroom teaching. This study investigates the relationship between Kathak dance–based cultural values in teaching practices and teaching effectiveness among secondary school teachers. A cross-sectional correlational survey design was employed. Data were collected from secondary school teachers using a structured Likert-scale questionnaire measuring Kathak-based cultural values in teaching and perceived teaching effectiveness. Descriptive statistics, reliability analysis, Pearson correlation, and regression analysis were used to analyze the data. The findings indicate a significant positive relationship between Kathak dance–based cultural values and teaching effectiveness. The results suggest that integrating culturally grounded pedagogical values inspired by Kathak can enhance instructional effectiveness in secondary education. This study contributes to the growing literature on culture-responsive pedagogy by highlighting the educational relevance of classical dance traditions in contemporary school teaching.